Solubilitas Gas CO2 dalam Larutan Potassium Karbonat - Khoirul Anam dan Yan Provinta, Kuswandi, (Jurnal Teknik Kimia, 2008)
The Carbon dioxide (CO2) gas is the product from nature source as specially from nature gas.Once methode for CO2 concentration reduction is absorption with potassium carbonate solution.This research is experimental study for performances increase in absorption process and wettedwall column as absorber concentration potassium carbonate varied in the range 10-30% (weight)and temperature varied in the range 30-60oC. Estimation calculation with vapor-liquid equilibriumand chemical reaction with ENRTI model. The result show that the value of mol CO reduction is with temperature increasse and Potassium Carbonate concentration increase. Compare estimation result with experimental show small different.